220 Preferentially oriented copper materials and their preparation and applications in metal negative electrodes and metal batteries
The copper material with an optimal orientation of 220 is prepared by electrolysis and used as a current collector of zinc ion batteries, solving the zinc dendrites and perforation problems of zinc foil negative electrodes, and achieving efficient zinc deposition/peeling and electrochemical performance improvements.
Patent Information
- Application Number
- CN202211225059.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-10-09
AI Technical Summary
The application of zinc foil negative electrodes in lithium-ion batteries is limited. Due to the problems of zinc dendrites and zinc foil perforation, the prior art is difficult to effectively solve these problems, and the inert current collector materials are costly.
The copper material with an optimal orientation of 220 is prepared by electrolytic method, and the relative texture coefficient of Cu(220) crystal surface is increased, and used as a current collector material to induce reversible deposition/peel of metal zinc.
Excellent metal zinc reversible deposition/peeling performance is achieved, the electrochemical performance of metal negative electrode is improved, the generation of zinc dendrites is reduced, and the cost is low.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal negative electrode current collector materials, and in particular relates to the field of metal negative electrodes. Background Art
[0002] Aqueous zinc-ion batteries with zinc metal as anode have the advantages of safety, environmental protection, and considerable energy density. They are expected to replace lithium-ion batteries in large-scale energy storage systems, thereby alleviating the resource and safety problems of lithium-ion batteries. However, the practical application of zinc foil anode is limited because it suffers from problems of zinc dendrites and zinc foil perforation, which is caused by irregular zinc deposition / stripping during cycling. The perforation problem of the electrode can be essentially solved by using an inert current collector, but the inhomogeneity of the substrate surface and the low zinc deposition activity will induce the formation of zinc dendrites. Its activity and heterogeneity problems can be alleviated by regulating the crystal plane orientation of the substrate surface. For example, a flat graphene decorative layer can achieve dense zinc deposition by inducing epitaxial growth of Zn(001), and copper nanowires with exposed Cu(111) crystal planes can promote uniform growth of zinc and nucleation. In addition, commercially expensive Cu(100) single crystals can also be used to suppress the formation of zinc dendrites. However, the prospects of graphene, copper nanowires, and copper single crystals for low-cost aqueous zinc-ion batteries are severely limited due to their high cost. Therefore, it is necessary to develop more efficient and low-cost regulation strategies for current collector materials.
[0003] Electrolytic copper foil is a widely used commercial current collector material due to its mature manufacturing technology and acceptable cost. Selective crystal face exposure during copper foil electrolysis has been shown to be easy to achieve and can be integrated into the existing copper foil preparation. Therefore, the preparation of copper foil with special orientation by electrolysis may be a promising method for practical application. Unfortunately, the copper electrolysis process may expose multiple crystal facets such as (111), (200), (220) and (311), and the zinc deposition activity of these crystal facets has not been fully studied, and it is impossible to determine which of the above crystal facets has the highest activity. If the most active crystal facet is identified, zinc deposition can be efficiently regulated by selectively exposing this crystal facet. Therefore, the preparation of copper current collector materials with highly active crystal facet exposure by electrolysis is very important for improving the reversibility of zinc deposition / stripping of the current collector. Summary of the invention
[0004] The first purpose of the present invention is to provide a 220 preferred oriented copper material, aiming to provide a material with excellent metal (such as metal zinc) reversible deposition / stripping properties and improved electrochemical performance of the prepared metal negative electrode.
[0005] The second object of the present invention is to provide a method for preparing the 220 preferred oriented copper material, aiming to provide a copper material that can prepare a high 220 texture coefficient and improve the electrochemical performance of the metal negative electrode.
[0006] The third object of the present invention is to provide the copper material with 220 preferred orientation as a current collector for inducing reversible deposition / stripping of metals such as metallic zinc to prepare a metallic zinc negative electrode.
[0007] The fourth object of the present invention is to provide a composite zinc negative electrode in which zinc metal is deposited on a copper material with a 220 preferred orientation, aiming to improve the reversible deposition / stripping of zinc in the zinc negative electrode and improve the electrochemical stability.
[0008] The fifth object of the present invention is to provide a method for preparing the composite zinc negative electrode and its application in a battery.
[0009] The sixth object of the present invention is to provide a metal zinc battery comprising the composite zinc negative electrode.
[0010] For copper materials with 220 preferred orientation, the relative texture coefficient of the Cu(220) crystal plane is ≥75%.
[0011] The present invention provides a copper material with a 220 crystal plane texture coefficient of ≥75%, and it is found that the 220 preferred oriented material has excellent metal reversible deposition / stripping performance, which helps to improve the electrochemical performance of the prepared metal negative electrode.
[0012] The present invention innovatively discovered that there is a positive correlation between the 220 preferred orientation and the metal deposition activity, and that increasing the (220) crystal plane relative texture coefficient helps improve the metal deposition activity and unexpectedly improves the electrochemical performance of the metal negative electrode.
[0013] In the present invention, the relative texture coefficient of the (220) crystal plane [TC(220)] accounts for the ratio of the total texture coefficient (TC) of the (111) crystal plane, (200) crystal plane, (220) crystal plane and (311) crystal plane of the copper layer [TC(220)].
[0014] Preferably, the relative texture coefficient of the Cu(220) crystal plane is ≥85%; more preferably 90%. Studies have found that the preferred copper material of the Cu(220) crystal plane helps to further improve the reversible deposition / stripping of the metal and helps to further improve the electrochemical performance of the prepared metal negative electrode.
[0015] Preferably, the copper material is a copper plane material (such as copper foil).
[0016] The present invention also provides a method for preparing the copper material with 220 preferred orientation, wherein copper is used as an anode and a deposition substrate is used as a cathode, and electroplating is performed in a copper plating solution to obtain the copper material with 220 preferred orientation;
[0017] The copper plating solution is an aqueous solution containing copper sulfate, sulfuric acid, a compound of formula 1 and an alkali metal chloride; wherein the concentration of CuSO4 is 100-250 g / L -1 ; The concentration of H2SO4 is 50-120gL -1 ; The compound of formula 1 is 0.05-0.2gL -1 ; The concentration of alkali metal chloride is 0.1-0.4gL -1 ;
[0018]
[0019] The n is 1 to 6; the M is H, Na or K;
[0020] The current density of the electroplating process is 100-200mAcm -2 .
[0021] The present invention innovatively discovers that by jointly controlling the composition, composition ratio and current density of the copper plating solution, synergy can be achieved, and a 220 orientation can be unexpectedly induced, which helps to obtain a copper material with a high 220 texture coefficient, excellent metal reversible deposition / stripping and improved electrochemical performance of the metal negative electrode.
[0022] In the present invention, the alkali metal chloride is at least one of sodium chloride and potassium chloride.
[0023] Preferably, in Formula 1, n is 2 to 4, preferably 3; and M is Na or K.
[0024] In the present invention, the joint control of the composition, composition ratio and current density of the electroplating solution is the key to synergistically inducing the 220 orientation.
[0025] Preferably, the concentration of CuSO4 in the plating solution is 150-200 g / L -1 ; The concentration of H2SO4 is 80-100gL -1 ; The compound of formula 1 is 0.1-0.2gL -1 ; The concentration of alkali metal chloride is 0.1-0.4gL -1 .
[0026] In the present invention, the concentration of each component of the electroplating solution refers to the ingredient metering concentration.
[0027] Preferably, the electroplating solution is a solution consisting of copper sulfate, sulfuric acid, the compound of formula 1, alkali metal chloride and water in the above amounts.
[0028] Preferably, the current density of the electroplating process is 100-120 mA cm -2 ;
[0029] Preferably, the electroplating treatment time is 6 to 10 minutes; more preferably 8 to 10 minutes.
[0030] In the present invention, the deposition substrate electrode may be any inert conductive substrate, such as stainless steel or titanium foil.
[0031] The present invention also provides an application of the 220 preferentially oriented copper material, which is used as a current collector for preparing a metal battery.
[0032] The preferred application of the present invention is to use it as a current collector to induce uniform metal deposition to prepare a composite metal negative electrode (a metal negative electrode with the current collector) of a metal battery.
[0033] The present invention innovatively discovered that there is a positive correlation between the 220 orientation and metal deposition, and increasing the 220 texture coefficient is helpful to improve the deposition activity of the metal and improve the electrochemical performance of the negative electrode after metal deposition.
[0034] In a preferred application, the metal is at least one of lithium, zinc and sodium; preferably zinc metal.
[0035] In a preferred application, the metal negative electrodes are assembled to form a metal battery; for example, a lithium metal battery, a zinc metal battery, etc.
[0036] The present invention also provides a composite zinc negative electrode, comprising the 220 preferred oriented copper material and metal zinc composited on the surface thereof.
[0037] In the present invention, a copper material with a preferred orientation of 220 is used as a current collector, which helps to induce the deposition of metallic zinc, so that the composite zinc negative electrode material can exhibit excellent electrochemical properties.
[0038] In the present invention, the 220 preferred oriented copper material is used as a current collector, and metal zinc can be deposited thereon based on existing methods to obtain the composite zinc negative electrode. For example, the composite zinc negative electrode can be obtained by electrochemical deposition.
[0039] The present invention also provides a method for preparing the composite zinc negative electrode, wherein metallic zinc is electro-deposited on the 220 preferentially oriented copper material to prepare the composite zinc negative electrode.
[0040] The preferred electrodeposition step is: using zinc anode and the 220 preferred oriented copper material as cathode, and conducting electrodeposition in a zinc plating solution containing zinc salt to obtain;
[0041] Preferably, the zinc salt is a water-soluble zinc salt, more preferably at least one of ZnSO4, ZnCl2, Zn (CH3COO)2, and zinc trifluoromethanesulfonate. There is no particular requirement for the concentration of the zinc salt, for example, it can be 0.5 to 5M.
[0042] Preferably, the current density of the electrodeposition is 1 mA cm -2 -50mAcm -2 .
[0043] In the present invention, the content of metallic zinc can be adjusted based on existing knowledge and application needs, for example, it can be 1 to 10 mAh cm -2 .
[0044] The present invention also provides the application of the composite zinc negative electrode, which is assembled to obtain a zinc metal battery.
[0045] In the present invention, the composite zinc negative electrode can be used as a negative electrode, and assembled with conventional electrical components and structures such as a positive electrode and a separator to form any battery with zinc metal as a negative electrode.
[0046] The present invention also provides a zinc metal battery, which comprises the composite zinc negative electrode.
[0047] The new metal battery of the present invention, in addition to using the composite zinc negative electrode of the present invention, other components and structures can be known. For example, the zinc metal battery is at least one of a zinc-manganese battery, a zinc-polyaniline battery, a zinc vanadate battery, and a zinc ion battery capacitor.
[0048] Electrochemical tests and morphological characterizations show that these Cu(220) highly preferred current collectors have highly reversible zinc deposition / stripping behaviors and exhibit dendrite-free zinc deposition morphology. Assembled Zn||MnO2 full battery tests show that the use of optimized copper current collectors can still maintain a capacity retention rate of 93.9% after 640 cycles, while the capacity retention rate of ordinary commercial electrolytic copper foil current collectors is only 44.2%.
[0049] Compared with the existing technology, the present invention has the following advantages:
[0050] (1) The present invention provides a copper material with a high texture coefficient of 220, and research has found that there is a positive correlation between the orientation content of the 220 and the reversible deposition / stripping of the metal.
[0051] The present invention uses an optical microscope combined with electron backscatter diffraction technology and an energy spectrometer for the first time to prove that the Cu(220) crystal plane has higher zinc deposition activity than Cu(111), Cu(200) and Cu(311), so achieving a high degree of Cu(220) crystal plane exposure is beneficial to improving the overall activity of the electrode. For example, copper foil with a (220) relative texture coefficient ≥75% can achieve highly reversible zinc deposition / stripping behavior using these highly active copper foils. This method of electrolytically regulating the crystal plane orientation of copper foil also has great application prospects in lithium metal battery current collectors.
[0052] (2) The present invention can unexpectedly achieve synergy through the combined control of the electroplating solution composition, component ratio and current density, and unexpectedly obtain a copper material with a (220) relative texture coefficient ≥ 75%, and the copper material can unexpectedly exhibit excellent induced metal reversible deposition / stripping performance and excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 a is an optical microscope photograph of the large-grain copper foil without zinc deposition;
[0054] Figure 1 b is the inverse pole figure obtained by electron backscatter diffraction test when the large-grain copper foil is not subjected to zinc deposition;
[0055] Figure 1 c is the confidence index graph obtained by electron backscatter diffraction when the large-grain copper foil is not subjected to zinc deposition;
[0056] Figure 1 d is an optical microscope image of a large-grain copper foil after a small amount of zinc deposition;
[0057] Figure 1 e is the electron backscattered image after zinc deposition;
[0058] Figure 1 f is the inverse pole figure after zinc deposition;
[0059] Figure 1 g is the confidence index image after zinc deposition;
[0060] Figure 1 h is the element distribution orientation at two locations after zinc deposition;
[0061] Figure 2 a is a scanning electron microscope image of a Cu(220) preferentially oriented copper foil (named P-Cu(220)) prepared by electrolysis;
[0062] Figure 2 b, c are electron photos and XRD patterns of the corresponding copper foils;
[0063] Figure 2 d is the inverse pole figure of P-Cu(220);
[0064] Figure 3 The scanning electron microscope images of the surface and cross section of commercial electrolytic copper foil (named C-Cu) and P-Cu (220) copper foil;
[0065] Figure 4 a is the cyclic voltammetry (CV) curve of the Zn||Cu half-cell;
[0066] Figure 4 b, c are the nucleation overpotential curves and results obtained from the three-electrode test;
[0067] Figure 4 d is C-Cu deposition 4mAhcm -2 SEM images of zinc.
[0068] Figure 4 ef is P-Cu(220) deposited 4mAhcm -2 Laser confocal microscopy and scanning electron microscopy images of zinc;
[0069] Figure 5 Deposition of 2 mAh cm for P-Cu(220) and C-Cu -2 SEM images of zinc.
[0070] Figure 6 Cycling performance images of half-cell and symmetric cells assembled with P-Cu(220) and C-Cu and zinc;
[0071] Figure 7 a is the SEM image of zinc after 50 cycles on P-Cu(220) and C-Cu;
[0072] Figure 7 b is the results of the cycle test after P-Cu (220) and C-Cu were assembled with MnO2 positive electrode after zinc plating. DETAILED DESCRIPTION
[0073] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0074] In the following cases, unless otherwise stated, the compound of formula 1 in the electroplating solution refers to formula 1-A:
[0075]
[0076] In the following cases, unless otherwise stated, the process for depositing metallic zinc on a copper current collector is:
[0077] Using metallic zinc as the anode and copper foil materials of different cases as the cathode, electrodeposition was carried out in a 1M zinc sulfate solution, and the zinc deposition content on the copper foil was 4 mAhcm -2 .
[0078] Example 1
[0079] In order to prove that the Cu(220) crystal plane has high zinc deposition activity, the present invention uses a copper foil with large grain size and random crystal orientation as the research object because it has good crystal plane recognition. This large grain copper foil can be prepared by annealing ordinary copper foil at 700℃ for 2h and then -2 Zinc was deposited for 20 s at a current density of , and then optical microscopy and electron backscatter diffraction tests were performed. An energy spectrometer was used to characterize the content of deposited zinc on the relevant grains, and finally the crystal plane with the highest zinc deposition activity was specified.
[0080] like Figure 1 As shown in Figure d, when a certain amount of zinc is deposited on the copper foil, there is a significant difference in glossiness on the surface of the copper foil, which is manifested in that some grains show obvious metallic luster, while some crystal faces do not undergo zinc deposition. Figure 1 a The copper foil without zinc deposition forms a sharp contrast. EBSD characterization shows that Figure 1 As shown in b and c, the copper foil without zinc deposition has a strong backscattered diffraction signal and no black noise appears, while the copper foil after zinc deposition has a strong backscattered diffraction signal and no black noise appears. Figure 1 As shown in e, f, and g, there are obvious black noise points concentrated. These black noise points come from the zinc that is preferentially deposited on the copper foil. The energy spectrometer also proves a conclusion. Figure 1 The zinc signal is more obvious on the grains where the black noise in e is concentrated. Then, the backscatter diffraction directional technology is used to indicate that these crystal planes that are easy to deposit zinc are Cu (220) crystal planes, while zinc is rarely deposited on Cu (111), Cu (200) and Cu (311). This is the conclusion proved for the first time by the present invention: Cu (220) crystal plane has higher zinc deposition activity than Cu (111), Cu (200) and Cu (311). This shows that the maximum exposure of the Cu (220) crystal plane is beneficial to improving the electrochemical activity of the substrate as a whole. Considering the strength of the copper foil and other issues, the present invention believes that when the texture coefficient of Cu (220) is ≥75%, it has excellent electrochemical performance.
[0081] Example 2
[0082] Based on the current mature electrolytic copper foil technology, the present invention adopts a scalable electrolytic method to prepare copper foil with Cu (220) preferred orientation. The specific preparation process and method are as follows: electroplating is performed using an electroplating liquid with the following composition: CuSO4 200gL -1 , H2SO480gL -1 , formula 1-A0.1gL -1 , NaCl0.2gL -1 . Use 120mAcm -2 The current density is 10 ... Figure 2 As shown in a, the surface of the prepared copper foil is composed of polyhedrons with a size of about 4 microns. Figure 2 As shown in b, this copper foil can be prepared on a small scale in the laboratory, and has a significant difference in glossiness compared with commercial electrolytic copper foil (this commercial copper foil is denoted as C-Cu, and the manufacturer is Nord Co., Ltd.).
[0083] like Figure 2 As shown in Figure c, XRD test shows that the main diffraction peak of the copper foil prepared by this electrolytic process is Cu(220), and its relative texture coefficient is calculated to be as high as 95% (this copper foil is denoted as highly preferentially oriented Cu(220) foil, referred to as P-Cu(220)), while the relative texture coefficient of the (220) crystal plane of ordinary commercial electrolytic copper foil (this copper foil is denoted as C-Cu) is only 67.7%. Figure 2 As shown in Figure d, P-Cu(220) has a strong (220) texture, indicating that the Cu(220) crystal plane is highly exposed on its surface. Figure 3 It shows that there is a significant difference in roughness between the electrolytically prepared copper foil and the commercial copper foil, but their thickness is not much different.
[0084] At the same time, different electrolyte formulas were used to prepare copper foils with different Cu(220) texture coefficients, as shown in Table 1.
[0085] Table 1 Relative texture coefficient of Cu(220) crystal plane of copper foil prepared using different plating solutions and electrolysis parameters
[0086]
[0087] Example 3
[0088] In order to further explore the zinc deposition performance of P-Cu (220) copper foil, the present invention uses zinc foil as the counter electrode, P-Cu (220) and C-Cu as working electrodes to assemble a battery for CV testing. Figure 4As shown in a, it can be found that P-Cu(220) has higher zinc deposition / stripping reversibility and extremely low nucleation overpotential. Using copper foil as the working electrode, zinc foil as the counter electrode, and Ag / AgCl as the reference electrode, the nucleation overpotential of different copper foils was accurately tested, as shown in Figure 4 b, c show that P-Cu(220) has a lower nucleation overpotential than C-Cu in a wide current density range, further indicating that the preference of the Cu(220) crystal surface can significantly improve the activity of the electrode. Figure 4 As shown in df, 4 mAh cm is deposited on the copper foil. -2 The results of SEM test showed that P-Cu(220) could deposit zinc densely and uniformly without zinc dendrites, while C-Cu produced obvious zinc dendrites due to its low electrode activity.
[0089] like Figure 5 As shown, further tests were performed at 5 mA cm -2 2 mAh cm was deposited at a current density of -2 The SEM of zinc can reveal that P-Cu(220) has dense zinc deposition, which further proves that the Cu(220) crystal plane is the active crystal plane for zinc deposition.
[0090] Example 4
[0091] The coulombic efficiency and cycle life of the Zn||Cu half-cell were tested using zinc foil as the counter electrode, copper foil (commercial copper foil and 220 copper foil with a texture factor of 95%) as the working electrode, and zinc acetate solution as the electrolyte. Figure 6 It can be seen that P-Cu(220) has a high coulombic efficiency and can be cycled for more than 1100 times without short circuit and coulombic efficiency reduction, while C-Cu has a low coulombic efficiency and a short circuit occurred after the 67th cycle, indicating that this highly preferentially oriented copper foil has a cycle life 15 times that of ordinary copper foil. -2 copper foil was used as the negative electrode to test its rate performance.
[0092] like Figure 6 As shown in Fig. 2b, P-Cu(220) can show a longer cycle life and a more stable voltage hysteresis, indicating that P-Cu(220) has a more excellent electrochemical performance. The deposition morphology of zinc on these copper foils was further tested. Figure 7As shown in a, the zinc on P-Cu (220) is still dense, while the zinc deposited on C-Cu shows obvious dendrite morphology. To further verify the practicality of this copper foil, we used galvanized copper foil as the negative electrode, commercial MnO2 material as the positive electrode, glass fiber as the separator, and zinc acetate solution as the electrolyte to assemble a CR-2025 button-type zinc ion full battery for testing. The MnO2 positive electrode sheet was prepared by rolling with a ratio of conductive carbon black: polytetrafluoroethylene binder: MnO2 of 1:1:8, and the loading amount of MnO2 active material was 5 mg cm -2 .like Figure 7 b Full battery test data show that the galvanized P-Cu (220) negative electrode can be cycled 640 times at a discharge depth of 20% and maintain a capacity retention rate of 93.9%, while the galvanized C-Cu has only a capacity retention rate of 44.2% after 640 cycles, further proving the practicality of this preferentially oriented copper foil.
[0093] The copper foils with different Cu (220) preferential orientations prepared in Example 2 were assembled into full batteries with MnO2 positive electrodes after galvanizing and tested. Their capacity retention rates are shown in Table 2 (640 cycles), which fully proves that the copper foil with a (220) texture coefficient ≥ 75% has better electrochemical properties.
[0094] Table 2 Electrochemical performance of full cells assembled using copper foils with different texture coefficients as current collectors
[0095]
[0096] It can be seen from Table 2 that the material with high 220 orientation prepared by the present invention can have excellent electrochemical properties.
[0097] Example 5
[0098] In order to prove the superiority of this copper current collector material with a texture coefficient of ≥75% in lithium metal batteries, we assembled a 2015 button battery for testing, using lithium iron phosphate material containing lithium ions as the positive electrode material, the positive electrode sheet was prepared by coating, and the positive electrode slurry was prepared by a ratio of conductive carbon: PVDF binder: lithium iron phosphate equal to 1:1:8, and then vacuum dried at 80 degrees for 12 hours; the negative electrode material does not use active lithium metal, but only uses copper current collector as the negative electrode (this battery is called a negative electrode-free lithium metal battery, and the active material of the negative electrode comes from the lithium metal deposited by the first charge, which can better prove the reversibility of the deposition and stripping of the current collector), using polypropylene film as a separator, and purchasing a commercial lithium metal battery electrolyte containing 2% lithium nitrate from Duoduo Reagent as the electrolyte for the full battery. The battery was assembled for testing, and the copper foil used was the samples numbered 4, 9, and 11 in Example 2 and the commercial copper foil C-Cu. Its specific initial capacity and capacity retention rate after 50 cycles are shown in Table 3: This shows that achieving a Cu (220) texture coefficient ≥ 75% can significantly improve the deposition / stripping reversibility of the copper current collector.
[0099] Table 3 Electrochemical performance of anode-free lithium metal full batteries assembled using copper foils with different texture coefficients as current collectors
[0100]
[0101]
[0102] In summary, the method described in the present invention can unexpectedly obtain a material with a 220 preferred orientation. Moreover, the material with a 220 preferred orientation has an excellent reversible induced metal deposition / stripping effect. Applying it to metal batteries can significantly improve the electrochemical performance of metal batteries.
[0103] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. 220 Preferentially oriented copper material, characterized in that: The relative texture coefficient of Cu(220) crystal plane is ≥75%; The preparation method of the copper material with 220 preferred orientation is as follows: using copper as an anode and a deposition substrate as a cathode, electroplating is performed in a copper plating solution to obtain the copper material with 220 preferred orientation; The copper plating solution is an aqueous solution containing copper sulfate, sulfuric acid, a compound of formula 1 and an alkali metal chloride; wherein the concentration of CuSO4 is 100-250 g / L -1 ; The concentration of H2SO4 is 50-120gL -1 ; The compound of formula 1 is 0.05-0.2gL -1 ; The concentration of alkali metal chloride is 0.1-0.4gL -1 ; The n is 1 to 6; the M is H, Na or K; The current density of the electroplating process is 100-200mAcm -2 .
2. The method for preparing the 220 preferred oriented copper material according to claim 1, characterized in that: CuSO4 concentration is 150~200gL -1 ; The concentration of H2SO4 is 80-100gL -1 ; The compound of formula 1 is 0.1-0.2gL -1 ; The concentration of alkali metal chloride is 0.1-0.4 gL -1 ; The electroplating solution is a solution consisting of copper sulfate, sulfuric acid, the compound of formula 1, alkali metal chloride and water in the above content; The current density of the electroplating process is 100-120mAcm -2 ; The electroplating treatment time is 6 to 10 minutes.
3. A 220 preferred oriented copper material according to any one of claims 1 to 2, characterized in that: It is used as a current collector to prepare metal batteries.
4. A 220 preferred oriented copper material according to any one of claims 1 to 2, characterized in that: It is used as a current collector to induce the deposition of metals and to prepare composite metal negative electrodes for metal batteries; The metal is at least one of lithium, zinc and sodium; The metal battery is a metal zinc battery.
5. A composite zinc negative electrode, characterized in that: The invention comprises the copper material with 220 preferred orientation as claimed in any one of claims 1 to 2, and metal zinc compounded on the surface of the copper material.
6. A method for preparing the composite zinc negative electrode according to claim 5, characterized in that: The composite zinc negative electrode is prepared by electrochemical deposition of metallic zinc on the 220 preferentially oriented copper material: The step of electrodeposition is: using zinc anode and the copper material with 220 preferred orientation as cathode, and conducting electrodeposition in a zinc plating solution containing zinc salt to obtain; The zinc salt is a water-soluble zinc salt, and the water-soluble zinc salt is at least one of ZnSO4, ZnCl2, Zn(CH3COO)2, and zinc trifluoromethanesulfonate; The current density of electrodeposition was 1 mA cm -2 -50mAcm -2 .
7. The use of the composite zinc negative electrode as claimed in claim 5, characterized in that: Assembling them to obtain a zinc metal battery; The zinc metal battery is at least one of a zinc-manganese battery, a zinc-polyaniline battery, a zinc vanadate battery, and a zinc ion battery capacitor.
8. A zinc metal battery, characterized in that: Comprising the composite zinc negative electrode as described in claim 6.
Citation Information
Patent Citations
Method for regulating and controlling crystal face orientation of metal material, metal material obtained through method and application of metal material
CN114480792A
Metal material obtained by method for regulating and controlling crystal face orientation of metal coating and application of metal material
CN114481101A
Electrolytic copper foil and method for producing the same
JP2011174146A